Genome-wide identification and expression characterization of ABCC-MRP transporters in hexaploid wheat - Bhati, Kaushal K.; Sharma, Shivani; Aggarwal, Sipla; Kaur, Mandeep; Shukla, Vishnu; Kaur, Jagdeep; Mantri, Shrikant; Pandey, Ajay K. (Frontiers in Plant Science, 2015)
The ABCC multidrug resistance associated proteins (ABCC-MRP), a subclass of ABC transporters are involved in multiple physiological processes that include cellular homeostasis, metal detoxification and transport of glutathione-conjugates. Although they are well studied in humans, yeast and Arabidopsis, limited efforts have been made to address their possible role in crop like wheat. In the present work, eighteen wheat ABCC-MRP proteins were identified that showed the uniform distribution with families of rice and Arabidopsis. Organ specific quantitative expression analysis of wheat ABCC genes indicated significantly higher accumulation in roots (TaABCC2, TaABCC3, and TaABCC11 and TaABCC12), stem (TaABCC1), leaves (TaABCC16 and TaABCC17), flag leaf (TaABCC14 and TaABCC15) and seeds (TaABCC6, TaABCC8, TaABCC12, TaABCC13 and TaABCC17) implicating their role in the respective tissues. Differential transcript expression patterns were observed for TaABCC genes during grain maturation speculating their role during seed development. Hormone treatment experiments indicated that some of the ABCC genes could be transcriptionally regulated during seed development. In the presence of Cd or hydrogen peroxide, distinct molecular expression of wheat ABCC genes was observed in the wheat seedlings, suggesting their possible role during heavy metal generated oxidative stress. Functional characterization of the wheat transporter, TaABCC13 a homolog of maize LPA1 confirms its role in glutathione-mediated detoxification pathway and is able to utilize adenine biosynthetic intermediates as a substrate. This is the first comprehensive inventory of wheat ABCC-MRP gene subfamily.